ChemInform Abstract: The Mild Thiolation, a Useful Tool for the Synthesis of Activated Building Blocks. Issue 3 (22nd January 2013) - Wuerfel, Hendryk; Weiss, Dieter; Beckert, Rainer
Abstract Review: 69 refs.